Benefit beliefs about protein supplements: A comparative study of users and non-users. (1st August 2016) - Hartmann, Christina; Siegrist, Michael
Abstract: The consumption of protein supplements among leisure time exercisers is growing. The present study aims to identify factors that motivate protein supplement consumption by comparing users' and non-users' underlying benefit beliefs about protein supplement. The study is based on an online survey of 813 Swiss adults (376 users of protein supplements and 437 non-users). Participants answered questions related to their benefit beliefs regarding protein supplement, their protein supplements consumption frequency, their activity level (GPAQ), and their reasons for taking protein supplement. In women, the most commonly cited reasons were to increase muscles (57.3%) and to regulate their weight (48.6%); and in men to increase muscles (83.7%) and to promote regeneration (53.7%). Furthermore, a principal component analysis revealed four benefit belief factors: (a) restore nutrients/avoid weakness; (b) fitness promotion; (c) health/well-being; (d) muscle modulation/competitive performance. The analysis showed that both users and non-users predominantly perceive protein supplements consumption as a strategy to modulate muscle mass, while beliefs in a health and well-being promoting effect was more prevalent among users ( M = 3.2, SD = 1.3) than non-users ( M = 2.7, SD = 1.3) (p < 0.001). Moreover, health and wellbeing-related beliefs were associated with an increased likelihood of a higher protein supplements intake frequency (OR = 1.5, 95% CI: 1.1–1.9), while physical activity level was not associated with protein supplements intake frequency. In addition, a negative correlation between physical activity level and beliefs in a fitness-promoting effect of protein supplements ( r = −0.14, p < 0.001) was observed, indicating that for a subgroup, protein supplements might license lower activity levels. Despite a lack of scientific evidence, consumers of varying activity levels consume protein supplements and believe in its' various positive features. Users should be better informed to prevent misguided health beliefs.